2022
DOI: 10.1109/access.2022.3191113
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition With Masks Based on Spatial Fine-Grained Frequency Domain Broadening

Abstract: Along with social distancing, wearing masks is an effective method of preventing the transmission of COVID-19 in the ongoing pandemic. However, masks occlude a large number of facial features, preventing facial recognition. The recognition rate of existing methods may be significantly reduced by the presence of masks. In this paper, we propose a method to effectively solve the problem of the lack of facial feature information needed to perform facial recognition on people wearing masks. The proposed approach u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Singh et al (2017) found that obscuring one's face with a mask, beard, sun glasses or scarf does not ensure one's face cannot still be recorded and identified. As mask mandates of the COVID-19 epidemic became commonplace, facial recognition models have since been optimized to work around face coverings, achieving only a 1% drop in accuracy as compared to unobscured faces (Chen et al, 2022). Even if there was a practical way for a customer to signal non-participation, retailers may not even be required to allow customers to opt-out.…”
Section: Privacy and Video Analyticsmentioning
confidence: 99%
“…Singh et al (2017) found that obscuring one's face with a mask, beard, sun glasses or scarf does not ensure one's face cannot still be recorded and identified. As mask mandates of the COVID-19 epidemic became commonplace, facial recognition models have since been optimized to work around face coverings, achieving only a 1% drop in accuracy as compared to unobscured faces (Chen et al, 2022). Even if there was a practical way for a customer to signal non-participation, retailers may not even be required to allow customers to opt-out.…”
Section: Privacy and Video Analyticsmentioning
confidence: 99%
“…First, the features of the unobscured areas of the eyes and forehead were obtained using a trained CNN model, and then a bag-of-features paradigm was used in the last layer of the network to quantify the features for classification. HUA-QUAN Chen et al [11] first obtained the unmasked eyes and forehead areas in the face image and used ESRGAN [12] to perform an image super-resolution. Next, the steps are divided into two parts based on the neural network.…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining the features from the three models, the EUM recognition results are evaluated using a self-restrained triplet loss. Chen et al [24] divided the process into four steps. The first step is to obtain the eye and forehead regions of the face image and perform image super-resolution using ESRGAN; the second step is to use the YCbCr color space in the image for frequency domain broadening analysis and then perform fast independent component analysis feature reduction to obtain features.…”
Section: Introductionmentioning
confidence: 99%